What Are the Economic Impacts of Indonesia’s Export Ban? A Computable General Equilibrium Analysis - Samir, Salman; Utami, Rizky; Razak, Muhammad Maula (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2024)
This study aims to assess the economic impact of the mineral export ban on Indonesia and other countries. The comparative-static version of the computable general equilibrium model (Global Tarde Analysis Project (GTAP)) is used to analyse the economic impact of the export ban, with a particular focus on GDP, welfare, terms of trade and external trade. The most recent GTAP version 9 database was used for the modelling simulations of the Indonesian export ban. The GTAP version 9 database has three reference years: 2004, 2007 and 2011. It already aggregates 140 regions and 57 sectors. The modelling simulation results show that the policy of bauxite, copper and tin export tyres benefits the Indonesian economy. Meanwhile, Indonesia’s export ban policy harmed the economies of other countries, particularly China, Japan, India, Korea and the EU-28.